A critical examination of the role of public participation in petroleum development contract in Nigeria. Issue 6 (8th March 2021) - Odion, Job Ohioma
Abstract : Purpose: The topic is examined with a view to ascertaining the various methods by which indigenous oil companies can participate in petroleum development contract in Nigeria. Also, the raison d'etre of the policy will be considered to see whether the government has achieved its primary aim and how successive government has approach the issue with a view to determining the best policy to adopt. The challenges facing this policy will be considered with a view to unfold whether the Petroleum Industry Bill proffers solution. Design/methodology/approach: This methodology of research is doctrinaire and analytical. The author used the available statute and case law in extrapolation of the views expressed in this paper; where necessary, secondary data as sourced from existing literature was used. Findings: This paper revealed that the existing laws in Nigeria do not support public participation in the petroleum sector. so much is in the hands of the government. The paper also found that this government's monopoly of the sector is one of the reasons for the slow level of development in the sector. Originality/value: This paper is original to the extent that it focusses on a relatively new area of public participation in the upstream petroleum sector in Nigeria. Most papers have often focussed on the downstream sector; however, this study seeks to re-direct the debate to the upstream sector.